SITCoM: SiRGraF Integrated Tool for Coronal dynaMics - Udhwani, Purvi; Shrivastav, Arpit Kumar; Patel, Ritesh (Frontiers in Astronomy and Space Sciences, 2023)
SiRGraF Integrated Tool for Coronal dynaMics (SITCoM) is based on the Simple Radial Gradient Filter used to filter the radial gradient in the white-light coronagraph images and bring out dynamic structures. SITCoM has been developed in Python and integrated with SunPy and can be installed by users with the command pip install sitcom. This enables the user to pass the white-light coronagraph data to the tool and generate radially filtered output with an option to save in various formats as required. We implemented the functionality of tracking the transients such as coronal mass ejections, outflows, and plasma blobs, using height–time plots and deriving their kinematics. In addition, SITCoM also supports oscillation and wave studies such as for streamer waves. This is performed by creating a distance–time plot at a user-defined location (artificial slice) and fitting a sinusoidal function to derive the properties of waves, such as time period, amplitude, and damping time (if any). We provide the option to manually or automatically select the data points to be used for fitting. SITCoM is a tool to analyze some properties of coronal dynamics quickly. We present an overview of the SITCoM with the applications for deriving coronal dynamics’ kinematics and oscillation properties. We discuss the limitations of this tool along with prospects for future improvement.